2017
DOI: 10.1111/hepr.12940
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PNPLA3 I148M polymorphism on histologically proven non‐alcoholic fatty liver disease in liver transplant recipients

Abstract: PNPLA3 I148M polymorphism can significantly affect histologically proven NAFLD at 1 year post-LT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 45 publications
1
17
4
Order By: Relevance
“…found that the G allele was a predictive factor in donors but not in recipients. These results differ from those in the previous study and those reported by Kim et al . Interestingly, however, Kim et al .…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…found that the G allele was a predictive factor in donors but not in recipients. These results differ from those in the previous study and those reported by Kim et al . Interestingly, however, Kim et al .…”
contrasting
confidence: 99%
“…These results differ from those in the previous study and those reported by Kim et al . Interestingly, however, Kim et al . also reported that the G allele in both the donor and recipient was the most important predictive factor; this is a very similar conclusion obtained by Dumortier et al ., who found that the development of NAFLD after LT was related to both the recipient (the “soil”) and the graft (the “seed”).…”
contrasting
confidence: 74%
See 1 more Smart Citation
“…Findings yielded by a small number of studies suggest that the PNPLA3-rs738409 G allele in either the donor or the recipient could be a risk factor for NAFLD recurrence or appearance after liver transplantation. 104,105 The potential value of using genetic markers for treatment decisions pertaining to patients enrolled in NASH clinical trials remains largely unexploited. Nonetheless, it is expected that this specific clinical application will be explored in the near future as the use of novel drugs for the treatment of NASH becomes available in the market.…”
Section: Genetics Of Nafld and Precision Medicinementioning
confidence: 99%
“…Mobilization of retinol from lipid droplets in HSC is catalyzed by REHs, and several enzymes are implicated in this process, including adipose triglyceride lipase (ATGL/PNPLA2) [ 44 ], patatin-like phospholipase domain-containing 3 (PNPLA3) [ 44 , 45 , 46 ], and hormone-sensitive lipase (HSL) [ 47 , 48 ]. Interestingly, genetic studies have identified the PNPLA3-I148M variant as a prominent genetic factor associated with NAFLD, and even more prominently with disease progression within NAFLD to NASH and NASH-associated cirrhosis [ 49 , 50 , 51 ]. PNPLA3 affects vitamin A homeostasis, as will be discussed in more detail in the following sections.…”
Section: Vitamin a Uptake Storage And Metabolismmentioning
confidence: 99%